2010
DOI: 10.1002/jor.21287
|View full text |Cite
|
Sign up to set email alerts
|

Polymethylmethacrylate and titanium alloy particles activate peripheral monocytes during periprosthetic inflammation and osteolysis

Abstract: ABSTRACT:We investigated the interactions of particulate PMMA or titanium alloy, patient blood monocytes, and periprosthetic tissues using a SCID-hu model of aseptic loosening. Periprosthetic tissues and bone chips obtained at revision surgery for loosening were transplanted into muscles of SCID mice. Peripheral blood monocytes (PBMCs) isolated from the same donors were fluorescently labeled and cocultured with PMMA or Ti-6Al-4V particles before intraperitoneal injection. Control mice with periprosthetic tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…Thirty‐three female severe combined immunodeficient (SCID) mice (CB17‐Prkdc SCID; Jackson Laboratory, Bar Harbor, Maine) at 3–4 weeks of age were quarantined in a pathogen‐free environment for at least one week before experimentation. When aseptic loosening patients underwent revision surgery, inflammatory periprosthetic tissue and bone chips were collected for implantation into the left quadriceps or paravertebral muscles of the SCID mice . Mice were intraperitoneally injected 20 µL of anti‐asialo GM1 rabbit sera (ASGM1, Wako Bioproducts, Inc., Richmond, VA) 4 h before human tissue implantation and again 7 days after surgery to eliminate the influence from host residual innate immune cells …”
Section: Methodsmentioning
confidence: 99%
“…Thirty‐three female severe combined immunodeficient (SCID) mice (CB17‐Prkdc SCID; Jackson Laboratory, Bar Harbor, Maine) at 3–4 weeks of age were quarantined in a pathogen‐free environment for at least one week before experimentation. When aseptic loosening patients underwent revision surgery, inflammatory periprosthetic tissue and bone chips were collected for implantation into the left quadriceps or paravertebral muscles of the SCID mice . Mice were intraperitoneally injected 20 µL of anti‐asialo GM1 rabbit sera (ASGM1, Wako Bioproducts, Inc., Richmond, VA) 4 h before human tissue implantation and again 7 days after surgery to eliminate the influence from host residual innate immune cells …”
Section: Methodsmentioning
confidence: 99%
“…It is generally accepted that the maturation and activation of osteoclasts (OCs) represent the principal pathology of aseptic loosening. As OCs are derived from osteoclast progenitor cells (OCPs) from the monocyte/macrophage lineage, recruitment of OCPs from blood and the generation of functional OCs at the interface between an implant component and the surrounding bone plays a critical role in periprosthetic osteolysis and bone resorption [9, 11, 12, 26]. As first noted in 1990, the in vitro maturation of osteoclasts requires the presence of marrow stromal cells or their osteoblast progenitor cells [27].…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages appear to be the key cells in responding to the stimulus of wear debris. We previously reported that various debris particles activated systemic human monocytes to traffic to and participate in the inflammation that characterizes the peri-prosthetic tissue associated aseptic loosening [11, 12]. Recently, wear debris has been shown to have an adverse effect on bone formation by bone marrow stromal cells [1, 1315], and in vitro studies suggested that osteoblasts play a pivotal role in osteoclastogenesis process through the production of RANKL and CSF-1 [16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that particle-provoked peripheral blood mononuclear cells participated in and promoted the local inflammatory process, osteoclastogenesis and bone resorption. 34 The initiation of an inflammatory reaction is the first mechanism used by macrophages when challenged by wear particles. Macrophages, as well as the other responding cells, secrete a number of cytokines, metalloproteinases, prostaglandins, lysosomal enzymes and growth factors, whose collective activities lead to an inflammatory reaction against debris, which in turn stimulates focal bone resorption at the bone-implant interface.…”
Section: Monocytes/macrophagesmentioning
confidence: 99%